2010
DOI: 10.1149/1.3392294
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated Polysulfone/POSS Nanofiber Composite Membranes for PEM Fuel Cells

Abstract: A class of nanofiber-based polymer/particle proton exchange membranes ͑PEMs͒ is described for use in H 2 /air fuel cells that operate at low humidity. The membranes were fabricated from electrospun nanofibers composed of sulfonated poly͑arylene ether sulfone͒ ͑sPAES͒ with sulfonated polyhedral oligomeric silsesquioxane ͑sPOSS͒ as a proton conductivity enhancer. The void space between nanofibers in an electrospun mat was filled with a mechanically robust and chemically stable UV-cross-linked polyurethane to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 27 publications
(26 reference statements)
4
45
1
1
Order By: Relevance
“…For example, densely sulfonated polysulfones with high molecular weights were successfully prepared via the direct copolymerization of sulfonated aromatic dihalides with various bisphenols. The corresponding dihalide comonomers, namely 3,3′‐disulfonated‐4,4′‐dichlorodiphenyl sulfone or 3,3′‐disulfonated‐4,4′‐difluorodiphenyl sulfone, were synthesized via the sulfonation of 4,4′‐dichlorodiphenyl sulfone or 4,4′‐difluorodiphenyl sulfone with 30% fuming sulfuric acid at 110 °C for 6 h under a nitrogen atmosphere . One of the major drawbacks in this preparation is higher degrees of sulfonation (above 50%), resulting in the formation of mechanically unstable polymers exhibiting excessive swelling.…”
Section: Chemical Functionalizationmentioning
confidence: 99%
“…For example, densely sulfonated polysulfones with high molecular weights were successfully prepared via the direct copolymerization of sulfonated aromatic dihalides with various bisphenols. The corresponding dihalide comonomers, namely 3,3′‐disulfonated‐4,4′‐dichlorodiphenyl sulfone or 3,3′‐disulfonated‐4,4′‐difluorodiphenyl sulfone, were synthesized via the sulfonation of 4,4′‐dichlorodiphenyl sulfone or 4,4′‐difluorodiphenyl sulfone with 30% fuming sulfuric acid at 110 °C for 6 h under a nitrogen atmosphere . One of the major drawbacks in this preparation is higher degrees of sulfonation (above 50%), resulting in the formation of mechanically unstable polymers exhibiting excessive swelling.…”
Section: Chemical Functionalizationmentioning
confidence: 99%
“…This approach involves electrospinning a polymer solution to obtain a nanofiber mat which is afterwards filled with a proton conductive polymer matrix [21][22][23][24][25][26][27][28], although insulating polymers infiltrated into proton conductive nanofibers has also been proposed [29,30]. Interestingly, it has been found that proton conducting nanofibers exponentially increase conductivity with decrease in fiber diameter [25,31].…”
Section: Introductionmentioning
confidence: 99%
“…Several inorganic nanomaterials, such as layered silicates (clay) [1,7,[55][56][57], silica [58][59][60][61][62][63][64], polyhedral oligomeric silsesquioxane [65,66], titanium dioxide [56,67,68], zirconium dioxide [69,70], heteropolyacids [27,71], carbon nanotubes [72][73][74][75][76], and graphene oxides [77,78], are being used for the fabrication of organic-inorganic hybrid membranes for both PEMFC and DMFC applications. Layered silicates are known for their high barrier property towards gases and solvents due to their unique layered and platelet type structure [79].…”
Section: Development Of Polymer Membranes For Fuel Cell Applicationsmentioning
confidence: 99%